Primary pleomorphic liposarcoma of the liver: a case report and literature review - Yuri Terunuma; Kazuhiro Takahashi; Manami Doi; Osamu Shimomura; Yoshihiro Miyazaki; Kinji Furuya; Shoko Moue; Yohei Owada; Koichi Ogawa; Yusuke Ohara; Yoshimasa Akashi; Shinji Hashimoto; et al. (Surgical Case Reports)
Abstract Background Primary liposarcoma arising from the liver is exceedingly rare. There have been very few reports documenting primary hepatic liposarcoma, especially of the pleomorphic subtype. Surgery is currently the only established treatment method, and the prognosis remains poor. In this report, we present an unusual case of hepatic liposarcoma of the pleomorphic subtype with literature review. In addition, we discuss theories regarding pathogenesis and the pathological and clinical features of primary hepatic liposarcoma to better outline this rare entity. Case presentation An asymptomatic 65-year-old female was found to have a right hepatic mass on a computed tomography scan 2 years after surgical resection of the left adrenal gland and kidney for adrenocortical carcinoma. Laboratory examinations were unremarkable. Magnetic resonance imaging demonstrated a 16-mm mass in the right hepatic lobe. Adrenocortical carcinoma metastasis was suspected. Laparoscopic partial hepatectomy completely removed the tumor with clear margins. Macroscopically, the surgical specimen contained a nodular, yellow–white mass lesion 20 mm in diameter. On pathologic examination, pleomorphic, spindle-shaped tumor cells containing hypochromatic, irregularly shaped nuclei of various sizes formed fascicular structures. Scattered lipoblasts intervened in varying stages. Mitotic cells were frequent. Ki-67 labeling index was 15%. Immunohistochemically, the tumor cells were diffusely positive for vimentin and focally positive for CD34 and alpha-SMA; lipoblasts were focally positive for S-100. Tumor cells were nonreactive for SF-1, inhibin alpha, desmin, HHF35, HMB45, Melan A, MITF, c-kit, DOG1, cytokeratin AE1/AE3, h-caldesmon, STAT6, CD68, MDM2, CDK4, c17, DHEAST, 3BHSD, CD31, Factor 8, and ERG. From these findings, primary hepatic liposarcoma of pleomorphic subtype was diagnosed. The tumor recurred intrahepatically 3 years later, and the patient died 5 months after recurrence. Conclusions In our report, we discussed the rarity, theories regarding pathogenesis, and a review of the literature of this atypical condition. To the best of our search, this is the 14th case of primary hepatic liposarcoma and the 2nd case of the pleomorphic subtype reported throughout the world. Further research regarding the etiology of this unusual clinical entity is warranted to establish effective diagnostic and management protocols.